1976
DOI: 10.1128/aem.32.3.381-387.1976
|View full text |Cite
|
Sign up to set email alerts
|

Factors affecting production of mold mycelium and protein in synthetic media

Abstract: The effects of certain cultural conditions on the yield of dry mycelium, protein, and total amino acid content of Rhizopus oligosporus Saito (NRRL 2710), Rhizopus rhizopodiformis (Cohn apud Lichtheim) Zopf (NRRL 6246), and Absidia corymbifera (Cohn) Sacc. et Trotter (NRRL 6247) were studied. The yield of mycelium was found to significantly increase as the spore inoculum was increased from 187,500 to 2,250,000 spores. But the total amino acids (grams/liter) did not change significantly, whereas the percentage o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

1981
1981
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(6 citation statements)
references
References 15 publications
0
6
0
Order By: Relevance
“…SSF on rice bran and N. intermedia SSF on okara due to fungal lipase activity for biomass production [ 73 75 ]. The increase in the total lipid content may be due to the fact that a high concentration of carbohydrate in stale bread favors the production of mycelial fat [ 76 ] or, as stated by Beuchat and Worthington [ 77 ], due to the selective utilization of non-lipid materials during cultivation. The fungus N. sitophila , among other fungi, was reported by the same authors to not utilize lipids during SSF of full-fat peanuts and preferential utilization of free fatty acids was not detected during the cultivation phase.…”
Section: Resultsmentioning
confidence: 99%
“…SSF on rice bran and N. intermedia SSF on okara due to fungal lipase activity for biomass production [ 73 75 ]. The increase in the total lipid content may be due to the fact that a high concentration of carbohydrate in stale bread favors the production of mycelial fat [ 76 ] or, as stated by Beuchat and Worthington [ 77 ], due to the selective utilization of non-lipid materials during cultivation. The fungus N. sitophila , among other fungi, was reported by the same authors to not utilize lipids during SSF of full-fat peanuts and preferential utilization of free fatty acids was not detected during the cultivation phase.…”
Section: Resultsmentioning
confidence: 99%
“…Figure 1b shows the schematics of the fungal biofilm reactor. Graham et al (1976) reported that the maximum yield of R. microsporus was obtained at a temperature of 378C and pH ranging from 3.0 to 5.0. Previous studies on suspended growth systems also showed that these parameters are optimal for fungal growth (Jin et al, 1999b;Van Leeuwen et al, 2003).…”
Section: Biofilm Reactormentioning
confidence: 99%
“…Since the availability of macro-and micro-nutrients has been reported to greatly impact fungal growth and survival (Moore-Landecker, 1996) and the corn wet-milling effluent had a low macro-nutrient content [nitrogen (N) and phosphorus (P)], additional N as (NH 4 ) 2 SO 4 and P as KH 2 PO 4 were added aseptically to the feed to maintain a COD:N:P ratio of 100:5:1, a typical ratio for biological growth. Trace metals, such as magnesium, iron and zinc were also supplied as suggested by Graham et al (1976).…”
Section: Attached Growth System With Pcs Medium Under Aseptic Conditionsmentioning
confidence: 99%
“…Different microorganisms consume specific _substrates at different rates due to their diverse metabolisms (Wainwright 1992). For example, Graham et al (1976) determined the yield of R. oligospo~us, l~hizopus fo~mis, and Aspe~gillus co~ymbife~a on different substrates and found that yield varied based on the microbial preferences (Table 2.8}.…”
Section: Effect Of Energy Sourcementioning
confidence: 99%